Adoption of Evidence-Based Clinical Innovations: The Case of Buprenorphine Use by Opioid Treatment Programs. (February 2014) - Andrews, Christina M.; D'Aunno, Thomas A.; Pollack, Harold A.; Friedmann, Peter D.
This article examines changes from 2005 to 2011 in the use of an evidence-based clinical innovation, buprenorphine use, among a nationally representative sample of opioid treatment programs and identifies characteristics associated with its adoption. We apply a model of the adoption of clinical innovations that focuses on the work needs and characteristics of staff; organizations' technical and social support for the innovation; local market dynamics and competition; and state policies governing the innovation. Results indicate that buprenorphine use increased 24% for detoxification and 47% for maintenance therapy between 2005 and 2011. Buprenorphine use was positively related to reliance on private insurance and availability of state subsidies to cover its cost and inversely related to the percentage of clients who injected opiates, county size, and local availability of methadone. The results indicate that financial incentives and market factors play important roles in opioid treatment programs' decisions to adopt evidence-based clinical innovations such as buprenorphine use.